The Dead Sea Scrolls in the Context of Hellenistic Judea : Proceedings of the Tenth Meeting of the International Organization for Qumran Studies (Aberdeen, 5-8 August, 2019) - Hartog, Pieter B.,; Perrin, Andrew B., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
Approaching the Qumran scrolls as an intrinsic part of Hellenistic and Roman antiquity, this volume shows how the authors and collectors of the Scrolls shared the interests of other inhabitants of the ancient Mediterranean and Near East and engaged in the same debates and dialogues as others in the Hellenistic and Roman periods. Thus, this volume offers an invitation to both Scrolls scholars and academics working on other disciplines to create opportunities for interdisciplinary research and exchange.